Three-Dimensional Analysis of Laminated Plates with Functionally Graded Layers by Two-Dimensional Numerical Model - PLUCIŃSKI, Piotr; JAŚKOWIEC, Jan (Engineering Transactions, 2020)
This work presents a three-dimensional (3D) numerical analysis of multi-layered laminated plates in which selected layers may be made of functionally graded material (FGM), in which the Young’s modulus may change along the thickness as a consequence of a continuous and graded mixture of two materials. For the analysis, the method, known as FEM23, is applied, which uses a two-dimensional (2D) mesh, yet enables obtaining full 3D results for the layered structure. In FEM23, the layered structure may be a combination of thin and thick layers made of materials with significantly different properties. This paper presents two examples comparing the results to other numerical or analytical solutions. The examples confirm the correctness and flexibility of FEM23 for laminated plates with functionally graded layers.